Synthetic chimeric nucleases function for efficient genome editing - R. M. Liu (Nature Portfolio, 2019)
CRISPR-Cas systems have well characterized, modular structures. Here the authors use that architecture to design a Cas12a library of 560 synthetic chimeras, with altered PAM preferences and specificities.